PELATIHAN PERAWATAN JANGKA PANJANG PADA LANSIA (PJP LANSIA) BAGI KADER POSYANDU LANSIA DI KABUPATEN MOJOKERTO - Yudha Laga Hadi Kusuma; Dwi Helynarti Syurandhari; Puspitaningsih, Dwiharini (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2023)
The developmental stage of the elderly is the final stage in a person's life cycle. During this time there are many changes and problems that can occur, but the elderly still need to get care when they have health problems. One of the activities that can be carried out to improve care efforts for the elderly is by providing long-term care training for the elderly. The purpose of this training is as a form of dedication from STIKES Majapahit lecturers to the community so that elderly posyandu cadres in Mojokerto Regency have the ability to provide long-term care for the elderly. This community service activity uses the Participatory Learning and Action (PLA) method. The PLA method enables the participation and activeness of the elderly posyandu cadres. Participants in this activity were elderly cadres throughout Mojokerto Regency, totaling 1,216 cadres from 27 Community Health Centers in the Mojokerto Regency area and carried out in 2 batches. The time for implementing this community service activity was carried out for 4 months, from September to November 2022. The results of this activity were an increase in knowledge of 91% and a positive attitude of cadres in terms of long-term care for the elderly by 89%.